PERAN KEUNGGULAN BERSAING MEMEDIASI PENGARUH INOVASI PRODUK TERHADAP KINERJA PEMASARAN UMKM PRODUK ENDEK DI DENPASAR - Luh Pande Suryaningsih; I Putu Gde Sukaatmadja; Ni Nyoman Kerti Yasa (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
ABSTRACT The purpose of this study is to explain the role of competitive advantage mediate the influence of product innovation on marketing performance at endow mnkm in Denpasar City This research was conducted in Denpasar City. The population used is the owner or manager of endek product MSEs. Sampling method used is purposive sampling. Data analysis used is path analysis and Sobel Test. Based on the analysis result found that product innovation have positive and significant effect to competitive advantage, product innovation have positive and significant effect to marketing performance, competitive advantage have positive and significant influence to marketing performance and competitive advantage have positive and significant influence in mediating product innovation to marketing performance. Suggestions on MSEs of endek products are expected to pay more attention to the innovation of products to be produced so as to compete.